Challenges of Treating Articular Pathologies - Nichols, Emma Hitt (MD Conference Express, 2014)
Treatment of articular cartilage and joint damage as a result of acute injury is challenging. This article addresses the particular topics of the basic science related to the early response of cartilage after traumatic injury, current and future chondroprotective products, osteochondral allografts, as well as chondroplasty, microfracture, and cells in relation to articular cartilage injuries.